2015
DOI: 10.1371/journal.pbio.1002133
|View full text |Cite
|
Sign up to set email alerts
|

Some Agreement on Kin Selection and Eusociality?

Abstract: The authors of "Relatedness, Conflict, and the Evolution of Eusociality" respond to objections raised by Martin Nowak and Benjamin Allen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The first is the publication of Nowak et al [4] (see also [5,6]). Personally, I have no basis to rule out the possibility that they may be right in their claim that the mathematics of inclusive fitness may be wrong or may have limited applicability [22] and there is no resolution in sight [21,23,24]. I am therefore more interested in their claim that old-fashioned, standard population genetic modelling can serve equally well (never mind whether better) in understanding the evolution of social behaviour.…”
Section: Why Then Look Beyond?mentioning
confidence: 99%
“…The first is the publication of Nowak et al [4] (see also [5,6]). Personally, I have no basis to rule out the possibility that they may be right in their claim that the mathematics of inclusive fitness may be wrong or may have limited applicability [22] and there is no resolution in sight [21,23,24]. I am therefore more interested in their claim that old-fashioned, standard population genetic modelling can serve equally well (never mind whether better) in understanding the evolution of social behaviour.…”
Section: Why Then Look Beyond?mentioning
confidence: 99%
“…Kin selection benefits related genes and improves inclusive fitness; this altruism is favored in two ways: kin recognition and viscous populations ( Hamilton, 1964 ). Most plants have limited dispersal, resulting in genetically structured populations within a small spatial scale ( Karban et al, 2015 ; Ehlers et al, 2016 ; Anten and Chen, 2021 ), leading to a high likelihood of interactions with related neighbors, and making kin recognition important ( Cheplick, 1992 ; Queller et al, 2015 ). Many previous studies provided evidence for kin recognition in plenty of plant species ( Dudley and File, 2007 ; Murphy and Dudley, 2009 ; Biedrzycki et al, 2010 ; Masclaux et al, 2010 ; Bhatt et al, 2011 ; Biernaskie, 2011 ; Simonsen et al, 2015 ; Zhang et al, 2016 ; Xu et al, 2021 ), and that showed kin recognition can act as a driver not only always reducing some competitive traits ( Dudley and File, 2007 ; Bhatt et al, 2011 ; Biernaskie, 2011 ; Crepy and Casal, 2015 ), but also sometimes increasing these competitive traits ( Milla et al, 2009 ; Murphy and Dudley, 2009 ; Masclaux et al, 2010 ; Mercer and Eppley, 2014 ).…”
Section: Introductionmentioning
confidence: 99%